CHEMICAL COMPOSITION AND BIOLOGICAL ACTIVITY OF THE ESSENTIAL OIL FROM CYMBOPOGON NARDUS (L.) RENDLE - Naidoo, N.; Thangaraj, K.; Odhav, B.; Baijnath, H. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The essential oil from the leaves, culms and rhizomes of Cymbopogon nardus were extracted and volatile oils were investigated for the first time using Gas Chromatography-Mass Spectroscopy (GC/MS). Alpha-cubebene, camphene, geraniol, limonene, myrcene, palmitic acid and sabinen were the major compounds identified. The essential oil was investigated for its antioxidant (DPPH assay), anti-inflammatory (5-lipoxygenase assay), antimicrobial (disk diffusion) and anti-mosquito properties (insecticidal, larvicidal and repellency assays). The oil showed poor antimicrobial activity and inhibited the growth of Bacillus, Micrococcus and Staphylococcus with a minimum inhibitory concentration of 0.0625 (vol/vol). The oil showed antioxidant activity, scavenging more than 80% of DPPH free radicals and did not show any anti-inflammatory activity. It also showed good adulticidal activity (53.7% mortality) and excellent larvicidal (100% mortality) and repellent activity (100% repellency) against Anopheles arabiensis mosquitoes, which are malarial vectors. The results of this study show that the essential oil from C. nardus possesses, antioxidant, antibacterial and anti-mosquito activities which may be associated with its predominant compounds viz., α-cubebene, camphene, geraniol, limonene, myrcene, palmitic acid and sabinen. These results lead the way for exploiting C. nardus oil as a multi-functional agent.